A Conceptual Model of Intention To Use Online Collaborative Consumption Platform - Lukni Burhanuddin Ahmad; Reza Ashari Nasution (School of Business, IPB University (SB-IPB), 2020)
The objective of this study is trying to develop a comprehensive model referring to previous research of Hwang and Griffith's model of intention to participate in Collaborative Consumption (CC). The study applied exploratory research design which implements previous researches regarding online collaborative consumption focusing on a study by Hwang and Griffith. Hwang and Griffith's model of intention to participate in Collaborative Consumption (CC) is unique in that it recognizes both attitudes and sympathy as the primary predictors of the intention to use the CC platform. The model is also relevant to CC as it encompasses different values, which are utilitarian, hedonic and symbolic. This Study results in a comprehensive model which incorporating several variables from previous studies, such as online initial trusts and perceived behavioral control. We conclude that by trying to put Technology Acceptance Model (TAM) and The Unified Theory of Acceptance and Use of Technology (UTAUT) will enrich the global-scale model from the higher point of view besides the cognitive perception itself. Moreover, this conceptual model is developed as a suggestion for future research as well as the implementation of more sophisticated statistical analysis method should be included. Keywords: digital business; startup; user intention; online market; collaborative consumption